Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/dac.3012
|View full text |Cite
|
Sign up to set email alerts
|

CCRA: channel criticality based resource allocation in cognitive radio networks

Abstract: In cognitive radio networks, signal to interference plus noise ratio (SINR) is a quantity that is used to analyze the bounds of the capacity of a channel. This is the reason for SINR being one of the important parameters toward evaluating the performance of spectrum sharing in every network. To maximize the channel utilization in any network, the SINR of a channel should be considered to be within a threshold. This also leads to lesser power consumption, and the quality of service for the licensed users is mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Such systems utilize various complex optimization techniques running at a central node to attempt an optimal distribution of the spectrum among the cognitive BSs. Such techniques include visualizing the network as a graph and then using graph theory to resolve conflicts between base stations (vertices) . Another approach is game theory, where the system is modeled as a centralized game with cognitive BSs being the players .…”
Section: Centralized Versus Distributedmentioning
confidence: 99%
“…Such systems utilize various complex optimization techniques running at a central node to attempt an optimal distribution of the spectrum among the cognitive BSs. Such techniques include visualizing the network as a graph and then using graph theory to resolve conflicts between base stations (vertices) . Another approach is game theory, where the system is modeled as a centralized game with cognitive BSs being the players .…”
Section: Centralized Versus Distributedmentioning
confidence: 99%
“…From the aforementioned study, it is observed that the SINR/interference of a channel is one of the important parameters toward channel allocation in CRNs. For better communication, the channel utilization and SINR are to be maximized according to (Xiao et al, 2012;Kumar and Minz, 2015). To overcome the limitations of the schemes discussed earlier in (Jiang et al, 2013;Bayhan and Alagöz, 2014;Jalali et al, 2015;Gelabert et al, 2010;Bedeer et al, 2014;Qin et al, 2009;Suliman et al, 2009;Wen et al, 2012;Wang et al, 2009;Mahdi et al, 2012) and for better utilization of channels, the authors of the work proposed in this paper were motivated to design a Multi Objective based channel allocation scheme in cognitive radio networks.…”
Section: Related Work and Backgroundmentioning
confidence: 99%